Property development: In search of an environmental sensitive development model - Verster, Basie (Acta Structilia, 2002)
The Quantity Surveyor (at times acting as principal agent or project manager) must become more pro-active, in the sense that returns, development costs, price, risk analyses and assessments are now crucial. To the quantity surveyor, this may sound like music to the ears, but if the profession is only concerned with the financial aspect of risk and return, there is an inherent danger that not only this generation, but also more specifically future generations, will be confronted with all the negative effects. This article proposes a model to assist with the management of the total impact of property development in an urban context. It also addresses the influence of property development on the rural environment.